FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS PADA IBU HAMIL DI RSUD dr. SOEHADI PRIJONEGORO SRAGEN - Anastavia, Nurima; Andhikatias, Yunia Renny (Jurnal Ilmu Keperawatan dan Kebidanan, 2025)
Abortion remains a serious maternal health issue in Indonesia, with various risk factors that can influence its occurrence. This study aims to determine the relationship between maternal age, parity, birth spacing, history of abortion, and hemoglobin levels with the incidence of abortion at Dr. Soehadi Prijonegoro General Hospital in Sragen. This study employed a cross-sectional design with a retrospective approach, utilizing medical records data from 84 pregnant women with abortion cases during the period from January to December 2024. Sampling was conducted using the total sampling method. Data analysis was performed using the Chi-Square test at a significance level of 0.05. The results showed a significant association between maternal age and the occurrence of abortion (p = 0.005; OR = 3.864), parity (p = 0.000; OR = 7.140), inter-pregnancy interval (p = 0.014; OR = 3.150), history of abortion (p = 0.000; OR = 6.963), and hemoglobin levels (p = 0.000; OR = 18.333). All variables studied had a statistically significant relationship with the occurrence of abortion, so it is important to consider these factors in efforts to prevent and monitor pregnancy.